PERENCANAAN KONSERVASI DAS BRINGIN BAGIAN HULU DENGAN CHECK DAM DAN SUMUR RESAPAN - Savitri Mustika Sari; Rizqi Fayunta A.; Joetata Hadihardaja; Suharyanto Suharyanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Changes in land use in the watershed Bringin affect the high rate of sedimentation watershed. This would result in the decrease as a function of watershed Bringin rainwater, recharge areas, water storage areas, catchers rainwater and drainage water. This condition will require a good handling in the field Bringin Watershed or in the river Bringin itself. The purpose of this research is to reduce sedimentation in the Bringin river caused by the erosion Bringin watershed. The research objective of these analyzes was to analyze the rate of erosion in the watershed Bringin and find solutions to overcome the erosion and sedimentation in Bringin. The method used in analyzing the rate of sedimentation in the Bringin watershed is a Universal Soil Loss Equation method (USLE). USLE method was used to predict the average rate of land erosion in the Bringin watershed. Input data required in this method is a USLE rainfall and runoff erosivity factor (R), soil erodibilitas factor (K), length-slope factor (Ls), land cover crops and crop management factors (C), and conservation measures practical factor (P). Results from the sedimentation rate analysis is a sediment yield of each sub-watershed on the Bringin watershed in units of tonnes / ha / yr. From nine sub-watersheds there are a critical sub-watersheds that is Bringin B9 sub-watershed with sediment discharge value of 23,963 tons / ha / yr over the allowable limit (10 tonnes / ha / yr). As a solution to control sedimentation rate is planning of sediment control construction (check dams) in Bringin B9 sub-watershed.